Variational determination of eigenstrain sources of residual stress - Korsunsky, A; Regino, G; Nowell, D (Tech Science Press, 2004)
If a distribution of inelastic strain (eigenstrain) in an engineering component is specified, together with the component geometry and the degree of constraint, then the residual stress field can be uniquely determined by elastic equilibrium. We address, using a variational approach, the inverst problem of eigenstrain determination from a set of measurements of residual stress or residual elastic strain.